2016
DOI: 10.1002/ptr.5648
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Polyphenols from Epilobium Angustifolium (Fireweed)

Abstract: Epilobium angustifolium is a medicinal plant used around the world in traditional medicine for the treatment of many disorders and ailments. Experimental studies have demonstrated that Epilobium extracts possess a broad range of pharmacological and therapeutic effects, including antioxidant, anti-proliferative, anti-inflammatory, antibacterial, and anti-aging properties. Flavonoids and ellagitannins, such as oenothein B, are among the compounds considered to be the primary biologically active components in Epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 156 publications
6
56
0
4
Order By: Relevance
“…Meanwhile, Epilobium is widely sold as dietary supplement all over the world. It is available in different pharmaceutical preparations, such as tinctures, capsules, pills, and creams (Pukhalskaya, Chernyakhovskaya, Petrova, Denisova, & Alieva, ; Schepetkin et al, ). Epilobium extracts can be bought singly, but many products are sold as combination pills, especially for “prostate health.” It is known that the amount of ingredients extracted from the plants may vary as a result of a number of factors, including genetic differences between species, part of the plants utilized, climatic and soil differences, time of harvest, storage of crude herb, and the extraction processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, Epilobium is widely sold as dietary supplement all over the world. It is available in different pharmaceutical preparations, such as tinctures, capsules, pills, and creams (Pukhalskaya, Chernyakhovskaya, Petrova, Denisova, & Alieva, ; Schepetkin et al, ). Epilobium extracts can be bought singly, but many products are sold as combination pills, especially for “prostate health.” It is known that the amount of ingredients extracted from the plants may vary as a result of a number of factors, including genetic differences between species, part of the plants utilized, climatic and soil differences, time of harvest, storage of crude herb, and the extraction processes.…”
Section: Discussionmentioning
confidence: 99%
“…This is the third review summarizing the pharmacotoxicological properties of Epilobium species (Granica et al, ; Schepetkin et al, ). It evidences that, although the use of Epilobium extracts is increasingly wider, understanding about their active compound/s and the mechanism/s of action remains lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition E. angustifolium extract exhibits an important antioxidant activity value: 179.57 ± 10.82 mmolTE/100g DW, measured by ORAC method. It is possible to conclude that the total phenolic content and the antioxidant activity are both very high in E. angustifolium, according with literatures (29). In fact experimental studies have demonstrated that E. angustifolium posses a broad range of pharmacological activity and therapeutic effects, including antioxidant, antiproliferative, anti-inflammatory, anti-bacterial and antiaging thanks to polyphenolic compounds, such as flavonoids, ellagitannins derivates, in particular oenothein B (10).…”
Section: Resultsmentioning
confidence: 72%